PERKEMBANGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENDUKUNG PENGGUNAAN MEDIA PEMBELAJARAN - Miranda; Darmansyah; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Learning media is a means of channeling learning messages and information. Learning media that are well designed really help students digest and understand the subject matter. The existence of learning media as a tool in the learning process is a fact that cannot be denied. The teacher as a messenger has a great interest in facilitating his task in conveying messages or learning materials to students. The teacher also realizes that without media, learning material will be difficult for students to digest and understand, especially if the learning material that must be delivered is complicated and complex. For this reason, the use of media is absolutely necessary so that material can reach students effectively and efficiently. In general, the benefits of media in the learning process are facilitating interactions between teachers and students so that learning activities will be more effective and efficient. The development of information technology in the current era of globalization and information has spurred the development of more advanced learning media as well. The use of Information and Communication Technology (ICT) as a learning medium is already a requirement. Although the design of ICT-based media requires special expertise, it does not mean that the media is avoided and abandoned. ICT-based learning media can be in the form of internet, intranet, mobile phone, and CD Room/Flash Disk. Advances in Information Technology have led to many changes.